Tổ chức phi chính phủ Quốc tế quan hệ đối tác vì sự phát triển : (VUFO-NGO resource centre, 2008)
This is the result from 20 sectors-specific Working Groups (WGs) operating under the NGO RC in 2008, including the newly established thematic groups under the Ho Chi Minh NGO Discussion group, each focusing on a specific area of development work in Vietnam.